Juridical Analysis Of Adultery Issues In Article 411 Of Law Number 1 Of 2023 On The Criminal Code - Hermalika, Yosi; Yusi, Suryani; Agustina, Sakinah (Fakultas Hukum Dehasen, 2025)
The title of this thesis is